Using Distance Technologies and Adaptive Pedagogical Practices as a Tool for High School Teachers - Inna I. Bobrova; Irina Yu. Efimova; Evgeny G. Trofimov (Современные информационные технологии и IT-образование, 2023)
The article presents an example of using an educational portal as a means of improving the educational process based on distance technologies and adaptive pedagogical practices, the active use of which in higher professional education transforms the educational environment of an educational institution into a high-tech environment with completely new didactic opportunities. Such opportunities make it possible to more effectively solve the important tasks of personality-oriented formation of graduates' competencies. The professional standard of a teacher pays close attention to the work of a teacher in implementing inclusive education programs, as well as supporting gifted and socially vulnerable students, the red thread is the possession of ICT competence, which is differentiated into three levels: general user, general pedagogical, subject-pedagogical. Such opportunities allow in a new way and more effectively to solve the important tasks of personality-oriented formation of graduates' competencies. One of the directions in solving this problem is the development of didactic teaching aids, such as electronic educational resources. The article shows the advantages of choosing a modular content structure when developing a course; ways to use tools to achieve adaptive practices are given; the advantages of using distance learning technologies are shown, which allow creating a single interactive workspace available to all participants in the educational process: students, teachers, administration. Thus, the authors show how an individual educational path is formed for each student, which guarantees the final development of the planned knowledge, skills and abilities. The use of distance technologies allows you to additionally form the skill of self-organization among students; introspection and self-discipline. There is a differentiation of the pace of learning; the motivation of acquiring knowledge increases; students develop a creative approach to learning; they learn to plan their study time and resources, and the teacher has an incentive to improve their competence in the field of pedagogy, psychology and information and communication technologies.